Cellular and molecular effects of n-3 polyunsaturated fatty acids on adipose tissue biology and metabolism - Flachs, Pavel; Rossmeisl, Martin; Bryhn, Morten; Kopecky, Jan (Clinical science (London, England, 2009)
Adipose tissue and its secreted products, adipokines, have a major role in the development of obesity-associated metabolic derangements including Type 2 diabetes. Conversely, obesity and its metabolic sequelae may be counteracted by modulating metabolism and secretory functions of adipose tissue. LC-PUFAs (long-chain polyunsaturated fatty acids) of the n-3 series, namely DHA (docosahexaenoic acid; C(22:6n-3)) and EPA (eicosapentaenoic acid; C(20:5n-3)), exert numerous beneficial effects, such as improvements in lipid metabolism and prevention of obesity and diabetes, which partially result from the metabolic action of n-3 LC-PUFAs in adipose tissue. Recent studies highlight the importance of mitochondria in adipose tissue for the maintenance of systemic insulin sensitivity. For instance, both n-3 LC-PUFAs and the antidiabetic drugs TZDs (thiazolidinediones) induce mitochondrial biogenesis and beta-oxidation. The activation of this 'metabolic switch' in adipocytes leads to a decrease in adiposity. Both n-3 LC-PUFAs and TZDs ameliorate a low-grade inflammation of adipose tissue associated with obesity and induce changes in the pattern of secreted adipokines, resulting in improved systemic insulin sensitivity. In contrast with TZDs, which act as agonists of PPARgamma (peroxisome-proliferator-activated receptor-gamma) and promote differentiation of adipocytes and adipose tissue growth, n-3 LC-PUFAs affect fat cells by different mechanisms, including the transcription factors PPARalpha and PPARdelta. Some of the effects of n-3 LC-PUFAs on adipose tissue depend on their active metabolites, especially eicosanoids. Thus treatments affecting adipose tissue by multiple mechanisms, such as combining n-3 LC-PUFAs with either caloric restriction or antidiabetic/anti-obesity drugs, should be explored.
Keywords: metabolický syndrom; tuková tkáň; metabolické sítě a dráhy; Adipocytes; Metabolic Syndrome; Animals; tukové buňky; Humans; lidé; Adipose Tissue; omega-3 mastné kyseliny; zvířata; proliferace buněk; Adipokines; Cell Proliferation; adipokiny; Metabolic Networks and Pathways; Fatty Acids, Omega-3